The Potential of AI as a Digital Tutor in Language Teaching English: A Review of the Literature - Sri agustina (Politeknik Siber Cerdika Internasional, 2025)
The increasing demand for personalized and effective English language learning remains a major challenge in conventional classrooms. This study aims to examine the potential of artificial intelligence (AI) as a digital tutor in English language teaching. This research employed a systematic literature review method by analyzing peer-reviewed journal articles, institutional reports (e.g., UNESCO and British Council), and empirical studies published between 2019–2024. The findings indicate that AI significantly improves English learning in five key areas: (1) personalized learning through adaptive systems, (2) increased student motivation and confidence, (3) enhancement of speaking skills via speech recognition technology, (4) improved teacher efficiency in assessment and material preparation, and (5) expanded access to quality education. Empirical studies show improvements in student performance ranging from 30–45%. However, challenges such as infrastructure limitations, digital literacy, data privacy, and over-reliance on technology remain critical concerns. In conclusion, AI functions effectively as a pedagogical partner rather than a replacement for teachers, with blended learning emerging as the most optimal approach for future English education.